Preparation of Ag/CuO Composites as Anode for Lithium-ion Batteries - Wang, C.; Li, N.; Li, D.Y.; Wang, F.F. (Asian Journal of Chemistry, 2015)
An Ag/CuO composite is obtained by a facile electroless deposition process and the electrochemical performance was evaluated for lithium-ion batteries application. The Ag/CuO composite electrode exhibit excellent cycle stability, retaining the capacity of 560 mAh g-1 at 0.1 C and 416 mAh g-1 at 1 C after 50 cycles, respectively within the voltage rage of 3-0.02 V (vs. Li+/Li). Furthermore, the composite electrode exhibits excellent rate capability at varying rates.